Peran Kepemimpinan Dalam Memotivasi Dan Meningkatkan Kinerja Karyawan PT. Pulau Sambu Desa Kuala Enok Kecamatan Tanah Merah Kabupaten Indragiri Hilir - Putri Wilhelmina; Efni Anita; Rabiyatul Alawiyah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Leadership is a science that comprehensively examines how to direct, influence and supervise others to carry out tasks in accordance with planned orders. motivation is a process of trying to influence someone to do something he wants. According to Amstron and Baron, performance is the result of work that has a strong relationship to the organization's strategic goals, customer satisfaction and makes an economic contribution. This research focuses on "The Role of Leadership in Motivating and Improving the Performance of Employees of PT Sambu Island, Kuala Enok Village, Tanah Merah District, Indragiri Hilir Regency". The objectives of this study are 1). To find out the role of leadership in motivating and improving the performance of employees of PT Sambu Island. 2). To find out the obstacles faced by leadership in motivating the performance of employees of PT Sambu Island. This type of research when viewed from the research plan can be classified into qualitative research. Based on the results of my research in chapter IV, it can be concluded, 1. That the leader or leader at PT.Pulau Sambu always strives so that in his leadership he can make employees always enthusiastic in carrying out the assigned tasks, the performance of employees at PT.Pulau Sambu has not yet reached the expected target because there are still employees who cannot complete their work according to the given target. 2. The obstacles faced by the leader or leader when motivating employees are that each employee has a different type or character. In overcoming the problem of motivating the leader or leader must further improve personal relationships with employees. By understanding the character and personality of employees, it will make it easier for the leader or leader to provide motivation.